ANALYSIS OF MOTHER’S KNOWLEDGE AND ATTITUDE ABOUT IMMUNIZATION HB0 - Masan, Lea (Krafon Publishing, 2019)
Hepatitis from various types is the biggest health problem in the whole world. Hepatitis has a large disease burden in the world, greater than other major infectious diseases, such as HIV, tuberculosis and malaria. The low coverage of HB0 immunization given less than 24 hours in infants is because some people do not or do not know the benefits of HB0 immunization should be given immediately after birth. This research is quantitative with a Cross Sectional approach. The sample was 30 mothers who had infants aged 0-2 months at the Primary Clinic IBI Sintang District Branch in 2018. The sampling technique used was purposive sampling method. The instrument of this study used a closed questionnaire. Data analysis using bivariate analysis with Chi Square test. The results showed that 67% of respondents were knowledgeable about giving HB0 immunization and 67% of respondents did not support HB0 immunization (67%). The results of statistical tests show that there is a relationship between knowledge and maternal attitudes about HB0 immunization (p=0.003).